Variable G protein determinants of GPCR coupling selectivity - Okashah, Najeah (Proc Natl Acad Sci U S A, 2019)
G protein-coupled receptors (GPCRs) activate four families of heterotrimeric G proteins, and individual receptors must select a subset of G proteins to produce appropriate cellular responses. Although the precise mechanisms of coupling selectivity are uncertain, the Gα subunit C terminus is widely believed to be the primary determinant recognized by cognate receptors. Here, we directly assess coupling between 14 representative GPCRs and 16 Gα subunits, including one wild-type Gα subunit from each of the four families and 12 chimeras with exchanged C termini. We use a sensitive bioluminescence resonance energy transfer (BRET) assay that provides control over both ligand and nucleotide binding, and allows direct comparison across G protein families. We find that the G(s)- and G(q)-coupled receptors we studied are relatively promiscuous and always couple to some extent to G(i1) heterotrimers. In contrast, G(i)-coupled receptors are more selective. Our results with Gα subunit chimeras show that the Gα C terminus is important for coupling selectivity, but no more so than the Gα subunit core. The relative importance of the Gα subunit core and C terminus is highly variable and, for some receptors, the Gα core is more important for selective coupling than the C terminus. Our results suggest general rules for GPCR-G protein coupling and demonstrate that the critical G protein determinants of selectivity vary widely, even for different receptors that couple to the same G protein.